1970
DOI: 10.1128/jb.101.1.92-101.1970
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Interactions in Cell Walls of Gram-Positive Cocci

Abstract: Isolated cell walls of Staphylococcus aureus and Micrococcus lysodeikticus were found to expand and contract in response to changes in environmental p H and ionic strength. These volume changes, which could amount to as much as a doubling of wall dextran-impermeable volume, were related to changes in electrostatic interactions among fixed, ionized groups in wall polymers, including peptidoglycans. S. aureus walls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…For the vast majority of bacteria, the rigid peptidoglycan cell wall dictates cell shape, independent of the membrane composition, and is the primary structure that bears the stress of turgor pressures on the order of atmospheres (Holtje, 1998;Scheffers and Pinho, 2005). In the absence of turgor pressure, the membrane will undergo plasmolysis and separate from the cell wall into highly invaginated structures (Ou and Marquis, 1970). How does one consider the physical effects of the com- A. Cardiolipin's unique dimeric structure, with two phosphatidyl head groups and four acyl chains, is indicative of a conical shape with a small radius of curvature Rlipid and hence a preference for highly curved geometries.…”
Section: Curvature-mediated Partitioning Of Phospholipidsmentioning
confidence: 99%
“…For the vast majority of bacteria, the rigid peptidoglycan cell wall dictates cell shape, independent of the membrane composition, and is the primary structure that bears the stress of turgor pressures on the order of atmospheres (Holtje, 1998;Scheffers and Pinho, 2005). In the absence of turgor pressure, the membrane will undergo plasmolysis and separate from the cell wall into highly invaginated structures (Ou and Marquis, 1970). How does one consider the physical effects of the com- A. Cardiolipin's unique dimeric structure, with two phosphatidyl head groups and four acyl chains, is indicative of a conical shape with a small radius of curvature Rlipid and hence a preference for highly curved geometries.…”
Section: Curvature-mediated Partitioning Of Phospholipidsmentioning
confidence: 99%
“…So far very little is known, at least quantitatively, of the relation between wall composition and surface properties in Gram positive bacteria. There is evidence that the relationship is not fixed but depends on evironmental conditions that can affect the state of expansion of the wall material [11] and the nature of the components that are exposed at the surface [12]. That we can obtain bacteria that contain controlled proportions of teichoic acid and teichuronic acid makes it possible to begin to study this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of salts to cell suspensions decreased cell volume, as also did Mg2+-acid glutaraldehyde solution, in contrast to either acid or alkaline glutaraldehyde without Mg2+. Changes in volume of the whole cell are considered to be due to ionic interaction of salts with the wall (Marquis 1968;Ou & Marquis 1970). Knowles (1971) suggested that an increase in turbidity of Esch.…”
Section: Discussionmentioning
confidence: 99%